Potential of Fuel Consumption Saving of Brayton Waste Heat Recovery Systems on Series Hybrid Electric Vehicles - Bou Nader, Wissam (2020)
In the global attempt to increase the powertrain overall efficiency of hybrid vehicles while reducing the battery size, engine waste heat recovery (WHR) systems are nowadays promising technologies. This is in particular interesting for series hybrid electric vehicles (SHEV), as the engine operates at a relative high load and under steady conditions. Therefore, the resulting high exhaust gas temperature presents the advantage of increased WHR efficiency. Brayton cycle offers a relative reduced weight compared to other WHR systems and present low complexity for integration in vehicles since it relies on open system architecture with air as working fluid, which consequently avoid the need for a condenser compared to Rankine systems. This paper investigates the potential of fuel consumption savings of a SHEV using Brayton cycle as WHR system from the internal combustion engine (ICE) exhaust gas. An exergy analysis is conducted on simple Brayton cycle and several Brayton waste heat recovery (BWHR) systems were identified. A SHEV with the ICE-BWHR systems are modelled, where the engine waste heat recovered is converted into electricity using an electric generator, and stored in the vehicle battery. Energy consumption simulations are performed on the worldwide-harmonized light vehicles test cycle (WLTC), considering the additional weight of the BWHR systems. The intercooled Brayton cycle (IBC) architecture is identified as the most promising for automotive application as it offers the most convenient compromise between high efficiency and low integration complexity. Results show 5.5% and 7.0% improved fuel economy on plug-in and self-sustaining SHEV configurations respectively, as compared to similar vehicle configurations with ICE auxiliary power unit. In addition to the fuel economy improvements, IBC-WHR system offers other intrinsic advantages such as low noise, low vibration, high durability which makes it a potential heat recovery system for integration in SHEV.